Comprehensive Analysis of lncRNA and miRNA Regulatory Network Reveals Potential Prognostic Non-coding RNA Involved in Breast Cancer Progression - Gao, Sheng; Lu, Xun; Ma, Jingjing; Zhou, Qian; Tang, RanRan; Fu, Ziyi; Wang, Fengliang; Lv, Mingming; Lu, Cheng (Frontiers in Genetics, 2021)
Breast cancer is one of the most common malignant tumors in women, and which is the second leading cause of cancer deaths among women. The tumorigenesis and progression of breast cancer are not well understood. The existed researches have indicated that noncoding RNAs, which mainly includes long noncoding RNA (lncRNA) and microRNA (miRNA), have gradually become important regulators of breast cancer. We aimed to screen the differential expression of miRNA and lncRNA in the different breast cancer stages and identify the key noncoding RNA using TCGA data. Based on Series Test of Cluster analysis, bioinformatics analysis and the negatively correlated relationships, 122 lncRNA, 67 miRNA, and 119 mRNA were selected to construct the regulatory network of lncRNA and miRNA. It was shown that miR-93/20b/106a/106b family was at the center of the regulatory network. Furthermore, 6 miRNAs, 10 lncRNAs, and 15 mRNAs were significantly associated with the overall survival (OS, log-rank P<0.05) patients with breast cancer. Overexpressed miR-93 in MCF-7 breast cancer cells were associated with suppressed expression of multiple lncRNAs, and these down-regulated lncRNAs (MESTIT1, LOC100128164 and DNMBP-AS1) were significantly associated with poor overall survival in breast cancer patients. Therefore, the miR-93/20b/106a/106b family at the core of the regulatory network discovered by our analysis above may be extremely important for the regulation of lncRNA expression and the progression of breast cancer. The identified key miRNA and lncRNA will enhance the understanding of molecular mechanisms of breast cancer progression. Targeting these key noncoding RNA may provide new therapeutic strategies for the breast cancer treatment and may prevent the progression of breast cancer from an early to an advanced stage.